«Em português, parecido com o da “Notícia de Torto”». The Earliest Documents in (Galician-)Portuguese Language and Father Avelino de Jesus da Costa - Souto Cabo, José António (Madrygal. Revista de Estudios Gallegos, 2024)
The name of Father Avelino de Jesus da Costa (1908-2000) is indissolubly linked to the question of the earliest texts written in (Galician-)Portuguese and, more generally, to written culture in Portugal during the initial phase of the Late Middle Ages. His contribution was fundamental in establishing the first framework for the oldest vernacular documents of Portuguese origin, a proposal that remained current throughout the final quarter of the twentieth century. In this article, we analyze and contextualize the work of the canon from Braga and present the developments, regarding the earliest texts in the vernacular, that have emerged from the end of that century to the present. One of the most noteworthy aspects is the unexpected discovery of Costa’s (anonymous) role in identifying the Pacto entre Gomes Pais y Ramiro Pais, certainly the most significant document among those we consider to have been written in Galician-Portuguese in the twelfth century.